The Influence of Ageing Process on the Barium Aluminate Phase Composition; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Bezmaternykh A. O. Anna Olegovna; Shvalev Yu. B. Yuri Borisovich; Kudiyarov V. N. Victor Nikolaevich; Gubin V. E. Vladimir Evgenievich; Babikhina (Babihina) M. N. Mariya Nikolaevna (2016, 2016)
Title screen